2006
DOI: 10.5688/aj700348
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Student Response to Patient-Simulation Mannequins to Teach Performance-based Pharmacotherapeutics

Abstract: Objective. To design and implement a simulated patient-case assessment using a mannequin for critical care pharmacotherapeutic education of doctor of pharmacy students and to evaluate student satisfaction with the simulation. Design. During the second year of the doctor of pharmacy program, all students were required to complete Introduction to Critical Care. This course consisted of didactic education, written patientcase sessions, and an interactive patient simulation session. Information on the patient case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 10 publications
4
91
1
1
Order By: Relevance
“…In relation to pharmacy education, anecdotal evidence suggests simple simulation techniques such as role plays and case studies are currently being used and have been for many years. There is some research available for the use of more complex and immersive experiential simulation techniques that have been used in pharmacy schools, to teach a range of technical and non-technical skills, including critical care [10], interdisciplinary teamwork [11], and pharmacotherapy skills [12].…”
Section: Introductionmentioning
confidence: 99%
“…In relation to pharmacy education, anecdotal evidence suggests simple simulation techniques such as role plays and case studies are currently being used and have been for many years. There is some research available for the use of more complex and immersive experiential simulation techniques that have been used in pharmacy schools, to teach a range of technical and non-technical skills, including critical care [10], interdisciplinary teamwork [11], and pharmacotherapy skills [12].…”
Section: Introductionmentioning
confidence: 99%
“…Barriers to implementing technology included student hesitation, 9,15,20 the need for technical support/oversight, 9,12,21,22 cost, 13,21,26 and resource utilization (eg, space, faculty time). 13,15,16,[19][20][21][22][23][24][25][26] …”
Section: Discussionmentioning
confidence: 99%
“…17 Results from an HPS study on myocardial infarction were higher, with an average examination score of 88% reported. 15 The use of HPS was well-received by students in these studies. Survey response rates were 93-100%.…”
Section: Human-patient Simulationmentioning
confidence: 99%
See 2 more Smart Citations